TOWARDS RESOLUTION: COMPARATIVE LESSONS FOR ADVANCING PEACE AND JUSTICE IN PAPUA - Hutapea, Tagor; Evan, Alexander (UI Scholars Hub, 2025)
The conflict in Papua represents a complex interplay of identity, sovereignty, and historical grievances, shaped by structural violence and socio-political exclusion. This study explores strategies for advancing peace-building and justice in Papua, drawing on Johan Galtung’s theory of peace and conflict and comparative lessons from the Aceh conflict in Indonesia and the Irish Republican Army’s (IRA) struggle in South Ireland. The findings emphasize the importance of addressing root causes such as historical injustices, economic inequality, and cultural exclusion. Inclusive governance and dialogues that respect ethnic diversity and local identities are critical to creating sustainable solutions. Case studies reveal that effective conflict resolution integrates local aspirations with broader national goals, utilizing participatory approaches to foster reconciliation and long-term stability. Lessons from Aceh and South Ireland underscore the need for transformative justice frameworks that prioritize structural change and community empowerment. This research contributes a comprehensive framework for addressing Papua's unique challenges by combining theoretical insights and practical lessons, advocating for policies that balance national unity with local self-determination. It calls for state and community collaboration to promote inclusivity, accountability, and sustainable peace in Papua.